PENGARUH ANGKATAN KERJA, INDUSTRIALISASI, INVESTASI, DAN TEKNOLOGI INFORMASI TERHADAP PDRB DI PULAU JAWA - Sabrina Ayunani, Nanda; Ida Nuraini (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2025)
This research analyzes the Gross Regional Domestic Product of all provinces on the island of Java, namely DKI Jakarta, East Java, West Java, Central Java, Yogyakarta and Banten. The aim of this research is to find out how labor force, industrialization, investment and information technology variables have an impact on gross regional domestic product (GRDP) on the island of Java. The research data is secondary data in the form of a time series from 2018 to 2023 originating from the central statistics agency of each province. The data analysis technique is panel data regression analysis. The selection of the best regression model is carried out through the Chow test, Hausman test and Lagrange multiplier test. The research results show that the labor force has a negative and significant influence on GRDP, the number of large and medium industries and the number of internet users have a positive and significant influence on GRDP, domestic and foreign investment have no influence on GRDP. It is recommended that local governments improve the quality of human resources, increase the number of industries, both large and medium, and make it easier for people to access the internet.